A Method for Public Parking Facilities Operation Condition Evaluation and Supply Scale Forecasting - Wang Yang; Wang Li-Juan; Wang Fan; Huang Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Based on the traditional  trip attraction model, a new method of operation condition evaluation and supply scale forecasting for public parking facilities is proposed. It begins with the operation condition investigation of existing parking facilities, and then analyzes qualitatively the existing parking facilities supply scale by four indexes. finally, it can calculate the supply scale in predict year. Combined with concrete work of urban parking facilities planning in china, the evaluation index and prediction model were applied, and the parking facilities operation condition, demand, supply scale and internal structure are analyzed deeply. The method proposed in the paper can provide the theory basis for the public parking facilities planning in other cities. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2069